2009
DOI: 10.1016/j.immuni.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A T Cell-Dependent Mechanism for the Induction of Human Mucosal Homing Immunoglobulin A-Secreting Plasmablasts

Abstract: Summary Mucosal IgA secreted by local plasma cells (PCs) is a critical component of mucosal immunity. Although IgA class switching can occur at mucosal sites, high-affinity PCs are optimally generated in germinal centers (GCs) in a T cell-dependent fashion. However, the mechanism of how CD4+ helper T cells induce mucosal-homing IgA-PCs remains unclear. We show here that TGFβ1 and IL-21, produced by follicular helper T cells (TFH), synergize to generate abundant IgA-plasmablasts (PBs). In the presence of IL-21,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 48 publications
5
111
0
4
Order By: Relevance
“…Therefore, the presence of CD103 + DCs may contribute to T-dependent and T-independent switching to IgA. One soluble factor associated with IgA induc-tion is TGF-b (49,50). We were unable to identify TGF-b production by freshly isolated CD103 + DCs ex vivo (data not shown), whereas surface-bound TGF-b was readily detectable on Tregs after sFliC (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, the presence of CD103 + DCs may contribute to T-dependent and T-independent switching to IgA. One soluble factor associated with IgA induc-tion is TGF-b (49,50). We were unable to identify TGF-b production by freshly isolated CD103 + DCs ex vivo (data not shown), whereas surface-bound TGF-b was readily detectable on Tregs after sFliC (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…One issue that will need to be addressed in greater detail is the relationship between Treg and T follicular helper cells in regulating switching to IgA. Although Treg responses in GCs have been shown to aid the specificity of the response and reduce the risk of autoimmunity (54), it is also likely that they can contribute to the magnitude of the switched response to IgA (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…T FH cells can arise in the absence of factors that mediate Th1, Th2, or Th17 differentiation, but depend on Bcl-6 (2-5). T FH cells express a high level of IL-21, which provides a robust stimulus for proliferation and differentiation of B cells (6,7). IL-21 also plays an indispensible role in the generation of T FH cells, probably by enhancing Bcl-6 expression (3).…”
Section: Cd28 ͉ Follicular B Helper T-cell ͉ Germinal Center ͉ Icos ͉mentioning
confidence: 99%
“…For example, the Th1 cytokine interferon-c (IFN-c) regulates immunoglobulin G2a (IgG2a) production, while the Th2 cytokine interleukin-4 (IL-4) is critical to IgG1/IgE class switching 5,6 and transforming growth factor-b (TGF-b) and IL-10 are implicated in the switch to IgA. 7 A recent study also suggested that IL-17 drives autoimmune responses by promoting the spontaneous formation of germinal centers, implicating Th17 cells in the regulation of autoreactive antibodies. 8 Recently, it has been elucidated that a subset of CD4…”
Section: Upon Encountering Their Cognate Antigens On the Surface Of Pmentioning
confidence: 99%